Alterations in Gene Expression of Renin-Angiotensin System Components and Related Proteins in Colorectal Cancer - Mehranfard, Danial; Perez, Gabriela; Rodriguez, Andres; Ladna, Julia M.; Neagra, Christopher T.; Goldstein, Benjamin; Carroll, Timothy; Tran, Alice; Trivedi, Malav; Speth, Robert C. (Journal of the Renin-Angiotensin-Aldosterone System, 2021)
Hypothesis/Introduction. Recent studies suggest involvement of the renin-angiotensin system (RAS) in cancers, including colorectal cancer (CRC). This study focuses on the association of genes encoding 17 proteins related to the RAS within a Japanese male CRC population. Materials and Methods. Quantitative expression of the RNA of these 17 genes in normal and cancerous tissues obtained using chip arrays from the public functional genomics data repository, Gene Expression Omnibus (GEO) application, was compared statistically. Results. Expression of four genes, AGT (angiotensinogen), ENPEP (aminopeptidase A) MME (neprilysin), and PREP (prolyl endopeptidase), was significantly upregulated in CRC specimens. Expression of REN (renin), THOP (thimet oligopeptidase), NLN (neurolysin), PRCP (prolyl carboxypeptidase), ANPEP (aminopeptidase N), and MAS1 (Mas receptor) was downregulated in CRC specimens. Conclusions. Presuming gene expression parallel protein expression, these results suggest that increased production of the angiotensinogen precursor of angiotensin (ANG) peptides, with the reduction of the enzymes that metabolize it to ANG II, can lead to accumulation of angiotensinogen in CRC tissues. Downregulation of THOP, NLN, PRCP, and MAS1 gene expression, whose proteins contribute to the ACE2/ANG 1-7/Mas axis, suggests that reduced activity of this RAS branch could be permissive for oncogenicity. Components of the RAS may be potential therapeutic targets for treatment of CRC.